Efektivitas Media Edukasi Digital dan Integratif dalam Meningkatkan Self-Management Pasien Diabetes Mellitus untuk Pencegahan Kegawatdaruratan Hiperglikemia - Tri Wahyuni Ismoyowati; Aryaprana Nando; Hari Iskandar Kang; Lido Sianipar (Journal of Innovative and Creativity (Joecy), 2026)
This literature review aimed to analyze the effectiveness of educational media in improving knowledge and self-management among patients with Diabetes Mellitus to prevent hyperglycemia emergencies. A systematic search was conducted across PubMed, Scopus, ProQuest, and Google Scholar for studies published between 2019–2024 using MeSH-based keywords related to diabetes education and self-management. Studies that met inclusion criteria involved adult diabetes patients receiving educational interventions through printed, audiovisual, or digital media. Findings showed that digital media, such as smartphone applications, interactive videos, telehealth, and gamification, consistently demonstrated significant improvements in knowledge, self-care behaviors, treatment adherence, and glycemic control. Audiovisual media also enhanced understanding and self-management skills, while printed media remained beneficial for older adults and individuals with limited digital literacy. Overall, multimodal educational strategies that combined digital and traditional media were most effective, particularly when supported by healthcare providers. These results indicated that educational media played a critical role in empowering diabetes patients to manage their disease and prevent hyperglycemia emergencies, including Diabetic Ketoacidosis and Hyperosmolar Hyperglycemic State.